A Fe/Fe3O4/N-carbon composite with hierarchical porous structure and in situ formed N-doped graphene-like layers for high-performance lithium ion batteries1. Issue 10 (14th March 2015) - Li, Yao; Meng, Qing; Zhu, Shen-min; Sun, Zeng-hui; Yang, Hao; Chen, Zhi-xin; Zhu, Cheng-ling; Guo, Zai-ping; Zhang, Di
<x xml:space="preserve">Abstract</x> A Fe/Fe3O4/N-carbon composite consisting of a porous carbon matrix containing a highly conductive N-doped graphene-like network and Fe/Fe3O4 nanoparticles was prepared.